Impact of tau and amyloid burden on glucose metabolism in Alzheimer's disease - Gérard N. Bischof; Frank Jessen; Klaus Fließbach; Julian Dronse; Jochen Hammes; Bernd Neumaier; Oezguer A. Onur; Gereon R. Fink; Juraj Kukolja; Alexander Drzezga; Thilo van Eimeren (2016)
Abstract In a multimodal PET imaging approach, we determined the differential contribution of neurofibrillary tangles (measured with [ 18 F] AV ‐1451) and beta‐amyloid burden (measured with [ 11 C]PiB) on degree of neurodegeneration (i.e., glucose metabolism measured with [ 18 F] FDG ‐ PET ) in patients with Alzheimer's disease. Across brain regions, we observed an interactive effect of beta‐amyloid burden and tau deposition on glucose metabolism which was most pronounced in the parietal lobe. Elevated beta‐amyloid burden was associated with a stronger influence of tau accumulation on glucose metabolism. Our data provide the first in vivo insights into the differential contribution of A β and tau to neurodegeneration in Alzheimer's disease.